Car Seat Swivel for Enhanced Accessibility for Disabled Individuals - Nazarudin , Waiz Uzair; Zairulnizam, Muhammad Amirul Haziqq; Mohammad Mohsein, Nur Miza Afiqah; Sidek, Noor Azizah; Nawawi, Azli (Multidisciplinary Applied Research and Innovation, 2025)
This project focuses on developing a car seat swivel mechanism tailored to improve mobility and comfort for individuals with leg disabilities. The innovation is centered on modifying Proton Saga car seats to allow rotational movement of up to 30 degrees, facilitating easier entry and exit. The design employs durable yet lightweight materials such as steel and aluminium, ensuring safety, stability, and ease of use. A manual swivel mechanism was chosen to minimize costs and simplify installation, making it an affordable and practical solution. The methodology involved analyzing existing seat slider technologies, user feedback, and ergonomic principles to create a user-centered design. Prototype testing revealed the swivel mechanism’s ability to support various user weights while maintaining stability and comfort. Enhancements included built-in safety features, such as secure locking mechanisms, and a compact design to prevent interference with the car interior. This project contributes to the field of assistive mobility technologies by offering an affordable, practical, and customizable solution for enhancing vehicle accessibility. Its focus on a specific user group and integration into a widely used vehicle model demonstrates significant potential for improving the quality of life for individuals with disabilities.